Association Between BAK1 Gene rs210138 Polymorphisms and Testicular Germ Cell Tumors: A Systematic Review and Meta-Analysis - Qin, Jiaxuan; Yang, Yufeng; Zhuang, Xuan; Xing, Jinchun (Frontiers in Endocrinology, 2020)
Background: Several studies including some genome-wide association studies (GWAS) had shown that BAK1 gene rs210138 polymorphisms might be associated with testicular germ cell tumors (TGCT). Here we tried to sum up the association through a systematic review and meta-analysis. Methods: Studies associated with BAK1 rs210138 and TGCT was systematically searched in databases. The effect size was pooled according to ORs and 95% CIs. Results: Our systematic review and meta‑analysis comprised 14 articles. Significantly increased risk of TGCT was found in eligible GWAS and follow-up studies, in overall group and its Caucasian subgroup. Conclusions: Compared with adenine (A), BAK1 rs210138 guanine (G) is associated with increased risk of TGCT. Well-planned studies with larger sample size and more subgroups are needed to verify the risk identified in our systematic review and meta‑analysis.